CODE-SWITCHING IN YOUTUBE VIDEO "KULIAH DILUAR LULUSNYA GAMPANG?" BY JAKARTA UNCENSORED - Gania Diah Iswari; Ni Luh Nyoman Seri Malini; I Made Suastra (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study aims to analyze the types, speech functions, and reasons for code-switching found in the YouTube video of Jakarta Uncensored entitled â€œKuliah Diluar Lulusnya Gampang?â€. The data was collected through the library research method. The data of this study was obtained by accessing the YouTube channel of Jakarta Uncensored. There are several theories applied in this study. The first theory is the types of code-switching proposed by Poplack (1995), the second theory is the speech functions of code-switching proposed by Appel and Musyken (1987), and the last theory is the reasons for code-switching proposed by Hoffman (1991). Based on the result of the analysis, there are three types of code-switching found in the video, namely tag switching, inter-sentential switching, and intra-sentential switching. Out of six different speech functions, there were five speech functions of code-switching found in the video, they are referential, directive, expressive, phatic, and metalinguistic. The reasons behind the occurrence of code-switching in the video are mostly because the speakers feel more comfortable using one language rather than another. There is also an occasion when the speaker wants to be emphatic about something. Aside from those two reasons, there are also several interjections and the intention of clarifying something found in the video.